(untitled) (Journal of the College of Basic Education, 2022)
The researcher used the programmed method, which is one of the self-learning methods, to identify its impact on the learners and to provide appropriate learning opportunities through the optimal investment of effort and time.The research aims to:1- Preparing an educational curriculum using programmed instruction in learning tactical exercises in handball.2- To identify the effect of the educational curriculum prepared by the programmed learning method in improving some physical abilities in the game of handball.